2005
DOI: 10.1016/j.homp.2005.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive homeopathic treatment in patients with severe sepsis: a randomized, double-blind, placebo-controlled trial in an intensive care unit

Abstract: Our data suggest that homeopathic treatment may be a useful additional therapeutic measure with a long-term benefit for severely septic patients admitted to the intensive care unit. A constraint to wider application of this method is the limited number of trained homeopaths.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 30 publications
0
50
0
6
Order By: Relevance
“…The question of whether homeopathy may treat critical illnesses such as sepsis and be useful in emergency conditions has been dealt with before now. [20][21][22] However, a word of caution must be added here. In India, all homeopathic physicians are medically trained doctors and therefore handling a septicemic case may be considered under their care.…”
Section: Discussionmentioning
confidence: 99%
“…The question of whether homeopathy may treat critical illnesses such as sepsis and be useful in emergency conditions has been dealt with before now. [20][21][22] However, a word of caution must be added here. In India, all homeopathic physicians are medically trained doctors and therefore handling a septicemic case may be considered under their care.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 22 trials (54%) reported both sample size calculations and intention to treat analyses. Eight trials (20%) did not report sample size calculations or intention to treat analyses (53,57,60,61,64,67,68,73). Four of these studies also had a methodological quality of B (medium quality) (53,64,67,73).…”
Section: Methodological Quality Of the Rctsmentioning
confidence: 99%
“…Auch am Inselspital Bern werden zusätzliche homöopathische Konsile in der Kinderonkologie angeboten, um die konventionelle Behandlung begleiten zu können [8]. Im AKH in Wien werden Tumorpatienten von Prof. Frass mit der Homöopathie begleitet und selbst auf der Intensivmedizin wird erfolgreich die Homöopathie eingesetzt [9]. Im Dr. Haunerschen Kinderspital der Phos.…”
Section: Diskussionunclassified